Criminal Offending and Mortality over the Full Life-Course: A 70-Year Follow-up of the Cambridge-Somerville Youth Study - Zane, Steven N. (Journal of quantitative criminology, 2019)
To investigate the relationship between criminal offending and mortality over the full life-course of treatment group participants in the Cambridge-Somerville Youth Study (CSYS).